PENGARUH KEPUASAN GAJI DAN KOMITMEN ORGANISASI TERHADAP INTENSI TURNOVER PADA DIVISI PT JAMSOSTEK - Handaru, Agung Wahyu; Muna, Nailul (Fakultas Ekonomi, Universitas Negeri Jakarta, 2012)
The purposes of this research are 1) to know description for pay satisfaction, organizational commitment, and turnover intention at PT Jamsostek 2) Test empirically influence of pay satisfaction toward turnover intention at PT Jamsostek 3) Test empirically influence of organizational commitment towards turnover intetion at PT Jamsostek 4) Test empirically influence of pay satisfaction and organizational commitment toward turnover intention at PT Jamsostek. The analysis used in this research are simple regresion and multiple regresion analysis. The method of this research is simple random sampling which has taken 60 employees from all divisions. Meanwhile the data was collected by using questionnaires and cultivated using SPSS 19.00. The result of t test for pay satisfaction is -2,12 and the signification is 0,04. This shows that there is an effect between pay satisfaction towards turnover intention. The result of t test for organizational commitment is -2,24 and the signification is 0,00 this shows that there is an effect between organizational commitment toward turnover intention. The result of F test is 29,403 and the signification is 0,00. This shows that there is an effect between pay satisfaction and organizational commitment towards turnover rintention. The result of R2 is 0,508 or 50,8%. It means turnover intention is affected by pay satisfaction and organizational commitment as much as 50,8% Keywords: Pay Satisfaction, Organizational Commitment, Turnover Intention